Antimicrobial Activity of Some Derivatives of Triacetic Lactone and Their Cd(II) and Hg(II) Complexes - SHAHID, SAMINA; MUGHAL, TAHIRA; ULLAH SHAH, HAMID (Asian Journal of Chemistry, 2012)
Triacetic lactone derived compounds and Cd(II) and Hg(II) complexes have been synthesized, characterized and screened for biological activities. Antibacterial activity was carried out against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Streptococcus pneumoniae, Bacillus subtilis, Streptococcus mutans and Sarcina lutae. In vitro antifungal activities were carried out against Trichoderma viridis, Aspergillus flavus, Fusarium laterifum, Aspergillus fumigatus, Candida albicans, Trichophyton mentogrophytes and Microsporum canis. The results of these studies showed that these metal complexes to be have more potential for antimicrobial activates as compared to the ligand. Cd(II) complex is more active against the all tested bacterial and fungal strains.